Recent developments in the synthesis of azaindoles from pyridine and pyrrole building blocks. Issue 3 (24th December 2020) - Motati, Damoder Reddy; Amaradhi, Radhika; Ganesh, Thota
Abstract : The azaindole framework is ubiquitous in bioactive natural products and pharmaceuticals. This review highlights the synthetic approaches to azaindoles with advantages and limitations, mechanistic pathways and biological importance. Abstract : The azaindole chemical scaffold is represented in many biologically active natural products and synthetic derivatives. Recently, this chemical scaffold yielded several therapeutic agents for a variety of diseases. Due to the interesting biochemical and biophysical properties of various isomeric azaindoles, numerous investigators have designed and implemented novel synthetic methods for azaindole core units in the past few decades. By using these novel strategies, a number of diversely substituted azaindoles including bioactive natural products, key intermediates and drug candidates have been produced. Herein, we have reviewed the novel synthetic strategies developed for azaindoles since 2011 and highlight their attractive reaction mechanisms, advantages and their limitations. This review may offer potential solutions to develop novel and facile methodologies for the azaindole derivatives of biological interest.